The athlete with type I diabetes: managing insulin, diet and exercise - Fahey, P. J.; Stallkamp, E. T.; Kwatra, S. (American Family Physician, 1996)
The numerous benefits of exercise for patients with insulin-dependent (type I) diabetes mellitus include an increase in insulin sensitivity and a reduction of blood glucose levels. However, competitive athletes with type I diabetes must be careful when planning to exercise. The most common potential complications in these athletes include exercise-induced hypoglycemia or hyperglycemia and postexercise hypoglycemia due to increased insulin sensitivity. With proper modifications of insulin dose and diet, plus careful blood glucose monitoring, athletes with type I diabetes can exercise safely and regularly. To prevent hypoglycemia, the insulin dose may need to be reduced by 30 or 50 percent before exercise. Avoiding regular insulin at bedtime and reducing the evening insulin dose may help prevent nocturnal hypoglycemia after exercise. A tailored diet should reduce the chance of hypoglycemia.